Cryopreservation of juvenile Mytilus galloprovincialis to safeguard mollusk biodiversity and support aquaculture - A. Lago; J. Troncoso; E. Paredes (Scientific Reports)
Abstract This study introduces groundbreaking cryopreservation, being the first to successfully cryopreserve the juvenile stage of a marine organism, the largest marine organism ever cryopreserved. By optimizing feeding strategies, equilibration times, and cryoprotectant concentrations, we extended our initial protocol for young larvae to include complex larval stages (72 h–26 days post-fertilization) and juveniles (40–45 days, up to 1 mm). These protocols mark a significant step in biodiversity conservation, seedstock preservation, genetic line maintenance, and sustainability of overexploited mollusk populations.